Pengaruh Incremental Capital Output Ratio, Indeks Pembangunan Manusia dan Upah Minimum Terhadap Pertumbuhan Ekonomi di Provinsi Lampung - Pebrianti, Juli; Yeni, Isra (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study aims to determine the effect of average years of schooling on poverty in Indonesia from 2012 - 2022. It also examines the impact of access to sanitation, government spending on the education sector, government spending on the health sector, and social assistance spending on poverty during the same period. This study uses secondary data sourced from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK). This research utilizes the panel data analysis method with a fixed effect model to analyze the data. The study findings indicate that average years of schooling, access to sanitation, and government spending on the education sector have a significant negative impact on poverty. Government expenditure in the health sector does not significantly impact poverty. The variable of social assistance expenditure has no negative and insignificant effect on poverty. Together, average years of schooling, access to sanitation, government spending on education and health sectors, and social assistance expenditure significantly influence poverty.